Penggunaan Perangkap Feromon dalam Studi Kepadatan Populasi, Kelimpahan, dan Sex Rasio Kumbang Badak Oryctes rhinoceros L. di Perkebunan Kelapa Sawit PTPN 1, Langsa, Aceh - Suwarno Suwarno; Tashania Tashania; Alia Rizki; Irvianty Irvianty; Cut Nanda Defira; Zuriana Siregar; Dahelmi Dahelmi (Universitas Syiah Kuala, 2026)
This study aims to estimate the population density, abundance, and sex ratio of rhinoceros beetles (Oryctes rhinoceros L.) at different growth phases of oil palm in PTPN I plantations, Langsa Baro District. This study was conducted from June to November 2023. The method used was an experimental method. Traps were installed in four sampling blocks, each covering an area of ​​20 Ha, namely immature plants (TBM), sand fruit phase (BP), productive plants aged 4-8 years (TM 4-8) and productive plants aged >10 years (TM >10). A total of eight trap units per plant growth phase were installed systematically with a distance between traps of 400 m. The results of the study obtained 100 individuals of rhinoceros beetles in all growth phases. The average population density was 1.25 individuals/Ha and abundance was 3,125 individuals/trap. Consistent pest management carried out in PTPN I oil palm plantations is suspected to affect the results obtained. The abundance of rhinoceros beetles trapped in the BP phase was the highest (4 individuals/trap) and was significantly different from the TM (4-8) and TM (>10) phases. There were more female rhinoceros beetle imagos trapped than male imagos, with a male:female sex ratio of 1:1.64. Future studies are needed to compare this with community-owned oil palm plantations, especially regarding the population and level of rhinoceros beetle infestation.